The story of my house - Ellwanger, George H. (George Herman), 1848-1906 (Salt Lake City, UT : Project Gutenberg, 2023)
"The Story of My House" by George H. Ellwanger is a reflective and descriptive piece written in the late 19th century. The work examines themes related to home, comfort, and the ideal domestic environment, providing a personal perspective on the significance of a house beyond mere structure, emphasizing its role in creating a nourishing and harmonious living space. The narrative draws from both the author's thoughts and references to various literary and philosophical influences as he explores the essence of an ideal home. At the start of the narrative, the author sets a contemplative tone, expressing his thoughts on the nature of a home and what constitutes the "perfect house." He introduces various elements that contribute to a house's character, emphasizing how a home should reflect individual tastes and preferences rather than conforming to architectural expectations. The opening portion presents a broad meditation on the challenges of building a perfect dwelling, touching upon the interplay between aesthetics, function, and the relationship to nature. Ellwanger's prose is rich with imagery that paints a picture of his surroundings, blending observations of nature's beauty with insights into the home-making process and its inherent complexities. (This is an automatically generated summary.)
Prologue -- The perfect house -- Old oriental masters -- Signs in the sky -- The ideal haven -- When leaves grow sere -- Decorative decorations -- My study windows -- My indoor garden -- A blue-violet salad -- Footsteps of spring -- Magicians of the shelves -- Authors and readers -- The pageant of the immortals -- Epilogue.
Release date is 2023-02-05
Charlene Taylor, Barry Abrahamsen, and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive/American Libraries.)
Keywords: Books and reading; Interior decoration; Architecture, Domestic